Global Perspectives on Sustainable Exit from Prostitution: An analysis of social enterprise approaches adopted by faith-based projects supporting women to leave prostitution - THORLBY, KATIE,ELAINE (2015)
Prostitution is highly contested and extensively researched yet despite the amount of research that has been carried out there has, until recently, been little focus on how people leave prostitution. Within the literature that does exist, the complexity of leaving prostitution is widely acknowledged. Exiting is seen as a process not an event, and one which is not necessarily linear, and studies recognise that those who seek to leave face multi-faceted barriers. The role of support organisations in facilitating transitions from prostitution is acknowledged but such organizations remain largely unexamined, as do the associations with faith traditions that have been noted amongst some of these organisations. The existing literature attests to the role of alternative employment in enabling women to exit and remain out of prostitution and a small number of empirical studies have begun to explore the role of micro-enterprise development and vocational skills training in the context of prostitution. The provision of alternative employment through the operation of a social enterprise, has, however, received scant attention. This thesis contributes to understandings of the process of exiting prostitution through an exploration of the phenomenon of faith-based projects that support women to leave prostitution through the operation of social enterprises. Based on data from an internet mapping study and ethnographic research with two case studies, a project in India and a project in the US, both of which are running social enterprises, the research examines the nature of such projects; how they support women to exit prostitution; how the social enterprise models employed by these projects operate; the salience of faith in the nature and work of such projects; and the experiences of the women engaging with these projects. In doing so, this thesis contributes to knowledge in three areas: (1) exiting prostitution, (2) social enterprise, and (3) faith